Manajemen Laboratorium Kesehatan Berbasis Standar Mutu pada UPTD LABKESDA Kota Serang : Studi Observasi - Aminatu Rokmah; Najwa Dewi Oka; Mario Mario; Olitia Pran Kuncoro Tarigan; Da’i Muhamad Rizkan; Asep Saefurrohman (Student Scientific Creativity Journal, 2026)
This study aims to determine the implementation of quality standard-based health laboratory management at UPTD LABKESDA Kota Serang. The focus of the study includes planning, implementation, supervision, and evaluation of quality standards in health laboratory services. This research employed a qualitative method with an observational study approach. Data collection techniques were conducted through observation, interviews, and documentation involving parties engaged in laboratory management. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that health laboratory management at UPTD LABKESDA Kota Serang has implemented quality standards in various aspects of service, including administrative management, quality control of examinations, management of facilities and infrastructure, and improvement of laboratory personnel competencies. However, several obstacles were still identified, such as limited human resources, supporting facilities that are not yet optimal, and the need for periodic supervision and evaluation improvements. The implementation of quality standard-based management is considered capable of improving the effectiveness of laboratory services and maintaining public trust in health examination results. Based on the findings, it can be concluded that the implementation of quality standard-based health laboratory management at UPTD LABKESDA Kota Serang has been carried out fairly w, although further improvements and developments are still needed to optimize the quality of laboratory services.